AN EMPIRICAL STUDY ON THE OPPORTUNITY AND CONSTRAINTS - BHAGWAN RAY (International Journal of Multidisciplinary Research and Studies, 2020)
The agricultural sector is a substantial contributor to the economy of India, and it is responsible for the employment of more than fifty percent of our total workforce. This sector has done an excellent job of boosting both its production and the level of cultivation it undertakes at each site. Although there has been an increase in population pressure, a decrease in the amount of land available per capita, and bad weather conditions over the course of the last three decades, the per capita availability of foodgrain at the national level has remained nearly the same at 465 grammes per day. This is despite the fact that there has been a decrease in the amount of land available per capita. With a total population of over 104 million people, it is the state with the third highest population density in the United States. DRPCAU, Pusa (Samastipur), Bihar, 1Principal Scientist (Agricultural Statistics) (email: 1Principal Scientist (Agricultural Principal Scientist in Agricultural Economics rediffmail.com), Principal Scientist in Agricultural Statistics (email address: While it only accounts for 2.9% of the entire landmass, India is home to around 9% of the total population of the nation.